Clinical Outcomes of Two-flap palatoplasty with Intravelar Veloplasty in Cleft Palate with/without Cleft Lip Patients in Uttaradit hospital - Kaewkumsan, Nadda (Health Science Clinical Research, 2020)
Objective: To determine the oronasal fistula formation following Two-flap palatoplasty with intravelar veloplasty for cleft palate repair. The complications including wound dehiscence, hematoma and wound infection were also assessed. Study Design: A retrospective descriptive study Methods: The study of consecutive cleft palate with/or without cleft lip patients who underwent Two-flap palatoplasty with intravelar veloplasty between July 2014 to February 2018 by a single surgeon. Demographic data including sex, cleft types, age at palatoplasty, the use of presurgical nasoalveolar molding (NAM), vomer flap, postoperative follow-up duration, operative time, blood loss and length of hospital stay (LOS) were recorded. Documented data were evaluated using statistical analysis. Results: Twenty-two patients were enrolled. There were 13 males and 9 females. The mean age at palatoplasty was 12.95 months (range: 10-28 months). The mean follow-up duration was 72.73 weeks (range: 4-180 weeks). The predominant cleft type was Veau 3 (45.5%) followed by Veau 2 (40.9%) and Veau 4 (13.6%). Twelve out of thirteen (92.3%) patients with Veau 3 and 4 had presurgical NAM. Four patients (18.2%) used the vomer flap. The average operative time was 65.23 minutes (range: 40- 140 minutes), mean blood loss was 13.86 ml. (range: 5-25ml) and mean LOS was 2.36 days (range:2-4 days). The oronasal fistula rate was zero percent. The immediate complications did not occurred. Conclusions: Two-flap palatoplasty with intravelar veloplasty is a successful technique for complete closure of cleft palate with low complications. No occurrence of oronasal fistula may result from the less severity of cleft types, presurgical NAM insertion and tension free closure maneuver techniques. Further study should determine long-term outcomes including speech and facial growth. Keywords: Two-flap palatoplasty, oronasal fistula, cleft palate